1996
DOI: 10.1002/(sici)1096-8652(199602)51:2<137::aid-ajh7>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia evolving from essential thrombocythemia in two patients treated with hydroxyurea

Abstract: Essential thrombocythemia (El) Is an uncommon myeloprollferatlve disorder, which is thought to develop from a multlpotent stem cell. Like other myeloprollferatlve diseases, ET is assoclated with an increased risk of development of acute leukemla (AL). However, the large majority of cases of leukemic transformation in ET are thought to be related to prior therapy, usually radioactive phosphorous or alkylatlng chemotherapy, and the development of AL In ET Is extremely rare In the untreated patient. in this repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…reported myeloid blastic transformation of ET treated with hydroxyurea, and they reported an increased incidence of 17p deletion in those patients (3). Myeloid blastic transformation in ET with chromosome abnormalities including trisomy 8 have also been reported in cases treated with hydroxyurea (9, 10). One of our four patients with blastic transformation with trisomy 8 had been treated with hydroxyurea, and the other three patients had been treated with busulfan or MCNU.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…reported myeloid blastic transformation of ET treated with hydroxyurea, and they reported an increased incidence of 17p deletion in those patients (3). Myeloid blastic transformation in ET with chromosome abnormalities including trisomy 8 have also been reported in cases treated with hydroxyurea (9, 10). One of our four patients with blastic transformation with trisomy 8 had been treated with hydroxyurea, and the other three patients had been treated with busulfan or MCNU.…”
Section: Discussionmentioning
confidence: 98%
“…Uozumi et al . summarized karyotype findings at blastic transformation of ET, and they found nine cases of trisomy 8 of 59 cases (15%) in which chromosome studies were performed (2–4, 9–12). After their report, one case of karyotype study at leukemic transformation was reported (13), but trisomy 8 was not found.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, whether asymptomatic and young ET patients should be treated and how, taking into account the known leukemogenic effect of cytotoxic agents. 28,29 Hydroxyurea does have leukemogenic potential, 29,30 a very important consideration when deciding whether or not to commit symptomatic younger patients with ET to continuous long-term therapy with this drug. The therapeutic effects of interferon in the treatment of ET include the effective control of thrombocytosis, reduction of splenomegaly and the control of disease-associated symptoms 31 but, although interferon is a nonleukemogenic agent, its cost and toxicity have prevented its widespread use.…”
Section: Discussionmentioning
confidence: 99%
“…Die Auffassungen reichen von völliger Unbedenklichkeit bis zur Empfehlung des vorsichtigen Einsatzes auch bei äl-teren Patienten [30][31][32][33][34][35]. Auf jeden Fall erhöht die konsekutive Anwendung von Busulfan und Hydroxyharnstoff das Leukämierisiko, so dass Busulfan nicht mehr angewendet werden soll.…”
Section: Zyto-bzw Thromboreduktive Therapieunclassified